4. Analisis Komparasi Pemberian Bantuan Amerika Serikat dalam Mengatasi Konflik Mali dan Sudan Selatan 2013-2015 - Andiny, Maudy Miya; Utomo, Tri Cahyo; Paramasatya, Satwika (Journal of International Relations, 2017)
Political and economic instability in Africa have caused more than 53 countries encounter conflict, including Mali and South Sudan. These ethnic conflicts have been observed from three parameters; political stability and the absence of violence, conflict barometer, and internal displaced person. To understand why these countries were decent to be putted in juxtaposition, this paper also explained about the geographical situation and its natural resources. On the other hand, to help resolve the ongoing conflicts, the United States of America becomes one of top aid donors in both countries respectively. However, the official aid provided by the USA has a significant difference amount of numbers. Hence, the conundrum of USA aid allocation was analyzed through neo-realism perspective on giving aid, geopolitics, and US Foreign Policy. These theoretical frameworks were pointed out the importance of international structure. Results indicated that the different amount of aid allocation was caused by the strategic interest in South Sudan. In conclusion, USA did not have interest neither in economic, political stability and democracy. USA was concerned about securing its strategic security in South Sudan from China’s geopolitics at recent time.